The National Geographic maps every foldout map from National Geographic magazine on CD-ROM. - National Geographic Society (U.S.). (National Geographic Society, 1998)
Includes National Geographic Magazine maps, 1888-Nov. 1959, and its later title, National Geographic, Dec. 1959-1997. Interactive map tours and time lines introduce the user to a rich collection of more than 500 maps.